EDGE BASED INTERPOLATION WITH REFINEMENT ALGORITHM USING EDGE STRENGTH FILTER FOR DIGITAL CAMERA IMAGES. - MARKKANDAN, S.; NARAYANAN, LAKSHMI; J., ROBERT THEIVADAS; SURESH, P. (Turkish Journal of Physiotherapy Rehabilitation, 2021)
A digital camera has become popular as many people are preferring a digital camera to take a picture. After recording the image, the performance in the digital camera should enable the user to view the captured image. The important role in the image processing chain is the interpolation of color-filter-array (CFA) or demosaicing. The color filter array (CFA) is the commercial framework widely adopted in the modern digital camera. The interpolation process has to be performed when the color information of the original image is filtered out. The reduction in the size and the cost of the camera depend on the sensor used in the digital camera with the color-filter-array (CFA). At each pixel position, only one color value can be estimated using CFA. The full-color image can be obtained through the estimation of all three colors at each pixel position and this process is known as demosaicing. The computer images are recognized with the usage of red (R), green (G), blue (B). The color image requires accurate edge related information which can be attained through edge oriented filter. With the available color, it is necessary to determine the remaining two colors to obtain the entire full-colored image. The missing component undergoes the interpolation process. The edge direction in the Bayer color-filter-array (CFA) is determined using the edge adaptive color demosaicing. The edge direction depends on spatial correlation on the Bayer color difference plane. The most common array is the Bayer CFA and this array involved in the measurement of green (G) image on a quincunx grid and, red (R) and blue (B) images on the rectangular grid. The human visual lies in the medium wavelength where the G images are measured at the higher sampling rate. The artifacts available in the reconstructed image undergoes the refinement process where it separates the low and high frequency using the low pass filter. The main aim of the proposed system model is to produce a high-quality image at a low consumption cost.